IMPLEMENTATION OF THE FLIPPED CLASSROOM LEARNING MODEL ON STUDENTS' MATHEMATICAL PROBLEM-SOLVING - Noviana Dini Rahmawati; Lilik Ariyanto; Zulfa Ardiyanti Khusna (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
The purpose of this study was to determine the problem solving ability of students who received the flipped classroom learning model better than the class that received the conventional learning model. The population in this study were students of class XI SMK N 1 Kudus. Sampling using simple random sampling with samples taken two classes, namely the experimental class and the control class. Data collection methods used are tests and documentation. Data analysis used two-way ANOVA test, post ANOVA test with Schefee method, and one-party proportion test. The conclusions are as follows: (1) the problem solving skills of students who get the flipped classroom learning model are better than the conventional learning model and (2) the problem solving abilities of students who use the blended learning and flipped classroom learning models achieve the Minimum Completeness Criteria.